Relaciones públicas y su incidencia en la imagen institucional de la Gobernación de Bolívar, cantón Guaranda, periodo mayo - septiembre 2023 - Hinojoza Fierro, Hermes Isaac (2024)
This study focuses on understanding the impact of public relations management on the institutional image of the Government of Bolívar, Guaranda canton, in the period May-September 2023. With the objective of identifying areas of strength and improvement in communication management. The importance of this analysis lies in understanding how external communication strategies can influence the perception of a government institution, especially at the local level, such as the Guaranda canton. This research is developed through scientific, inductive and deductive methods, with a mixed approach. Tools such as interviews, surveys and documentary analysis were used to collect information, which revealed results such as improving public relations management and the mostly positive perception of the institutional image of the Government in the Guaranda canton. In conclusion, this study demonstrates that adequate public relations management can have a significant impact on the institutional image, improving the perception of the institution and its credibility among citizens, and strengthening its relationship with the community in the Guaranda canton.